2021
DOI: 10.3389/fonc.2020.619085
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy in AML

Abstract: Recent advances in therapeutics coupled with steady improvements in supportive care for patients with acute myeloid leukemia (AML) have led to improved outcomes. Despite these advances, even in patients that achieve a complete remission with initial therapy high rates of relapse remain a clinical dilemma. For decades, investigators have attempted strategies of maintenance therapy to prolong both remission duration and overall survival in patients with AML. These approaches have included cytotoxic chemotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Recently, a randomized clinical trial (EURADRACT 2010–018,539–16) assessed the efficacy of maintenance therapy with Sorafenib in the setting of FLT3+AML who underwent allogeneic HSCT. This clinical trial showed a significant benefit in terms of overall survival and relapse free survival in the study arm versus the control group who received placebo [ 10 ,11]. Moreover, data about the use of TKI for extramedullary relapse of FLT3 AML after allogeneic HSCT are still very scarce [ 1 , 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a randomized clinical trial (EURADRACT 2010–018,539–16) assessed the efficacy of maintenance therapy with Sorafenib in the setting of FLT3+AML who underwent allogeneic HSCT. This clinical trial showed a significant benefit in terms of overall survival and relapse free survival in the study arm versus the control group who received placebo [ 10 ,11]. Moreover, data about the use of TKI for extramedullary relapse of FLT3 AML after allogeneic HSCT are still very scarce [ 1 , 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this single experience, treatment with Gilteritinib can be defined as manageable and safe with a low cardiac toxicity occurrence, although it was administered during GVHD. Worthy of note, the 2 nd allogeneic HSCT was performed without immunosuppression in order to enhance the graft versus leukemia effect of the transplant procedure and this choice determined the onset of grade IV aGVHD followed by extensive cGVHD [ 5 , 9 , 10 ]. However, although a full donor chimerism and the persistent hematological CR after the second allograft, the occurrence of leukemic breast localization confirmed the possibility of blast cells escapement as mechanism of action for AML relapse, also in presence of aGVHD, underlying the potential dissociation between graft versus leukemia and host effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral azacitidine was subsequently studied as maintenance therapy in AML, a setting in which no drug had previously been shown to provide a survival advantage. 53 In the QUAZAR AML-001 study, patients with AML who were 55 years or older and who were in first remission after intensive chemotherapy, with or without consolidation therapy, but were considered to be ineligible for hematopoietic stem cell transplantation (HSCT) were enrolled. 54 Patients were randomized to receive either oral azacitidine 300 mg daily or placebo on days 1 to 14 of repeated 28-day cycles.…”
Section: Oral Azacitidinementioning
confidence: 99%
“…Post-transplant maintenance for AML dates back to the 1960s, when chemotherapeutic agents and/or early immunotherapies such as interferon were trialed (6,7). The use of these agents was not broadly adopted due to both their high degree of toxicity and the unclear survival benefit (8). More recently, there has been a groundswell of interest in the use of novel therapeutic agents as maintenance therapy after allogeneic stem cell transplant, leveraging new understanding and identification of genetic mutations, epigenetic influences, and cell-signaling pathways which play critical roles in the behavior of leukemic cells combined with the more favorable toxicity profiles of these agents (7,8).…”
Section: Introductionmentioning
confidence: 99%